2014
DOI: 10.1016/j.fbio.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drying method and extraction variables on the antioxidant properties of persimmon leaves

Abstract: The presence of antioxidant compounds and therefore the antioxidant capacity of persimmon leaves and their extracts have been reported by many authors. Furthermore, it is known that both the method of drying and the temperature at which this process takes place substantially affect the properties of the final product. However, there are no studies in the literature that examine how drying variables can affect the quality of persimmon leaves, especially as refers to preservation of their antioxidant properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 30 publications
3
33
2
Order By: Relevance
“…High antioxidant potential of persimmon leaves has also been reported in previous studies (Martínez-Las Heras et al, 2014;Lim and Lee, 2016). The results of the present study showed that persimmon tea samples contain good antioxidant potentials.…”
Section: Antioxidant Activity Of Persimmon Seed Teasupporting
confidence: 70%
“…High antioxidant potential of persimmon leaves has also been reported in previous studies (Martínez-Las Heras et al, 2014;Lim and Lee, 2016). The results of the present study showed that persimmon tea samples contain good antioxidant potentials.…”
Section: Antioxidant Activity Of Persimmon Seed Teasupporting
confidence: 70%
“…Both values of biologically active compounds of freeze dried samples were inferior. This result is contrary to common view, because freeze drying is known to be a mild drying technology, but in some cases, the antioxidant activity in freeze dried samples were lower, than conventional 100°C air dried samples [9]. The higher values of biological active components at hot-air drying could be explained by the measuring method, which might be sensitive to compounds, formed by thermal treatment.…”
Section: Biologically Active Compoundscontrasting
confidence: 54%
“…Martínez-Las Heras et al [35] reported that extraction conditions affect the extractability of the antioxidant compounds.…”
Section: Antioxidant Potentialmentioning
confidence: 99%